2005
DOI: 10.1016/j.virol.2004.08.041
|View full text |Cite
|
Sign up to set email alerts
|

In vitro simian virus 40 large tumor antigen expression correlates with differential immune responses following DNA immunization

Abstract: Simian virus 40 (SV40) contains an essential protein, large tumor antigen (Tag), which assists in viral replication and causes cell transformation and immortalization. Our laboratory has examined plasmid DNA, expressing SV40 Tag under two different promoters, for use in potential cancer vaccination strategies. One plasmid, pSV3-neo, failed to induce SV40 Tag antibody, produced a weak cell-mediated response, and only partial protection in murine experimental tumor challenge systems. The second plasmid, pCMV-Tag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…Previous work from our laboratory has indicated a required initial role for SV40 Tag-specific antibody in achieving complete protection from mKSA tumor development when recombinant protein or plasmid DNA is utilized as a prophylactic vaccine (4,19,31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work from our laboratory has indicated a required initial role for SV40 Tag-specific antibody in achieving complete protection from mKSA tumor development when recombinant protein or plasmid DNA is utilized as a prophylactic vaccine (4,19,31).…”
Section: Resultsmentioning
confidence: 99%
“…SV40 Tag IgG antibody was detected in sera from immunized mice through indirect enzyme-linked immunosorbent assay (ELISA) as described by our laboratory (17,19). Briefly, 200 ng of recombinant SV40 Tag in boratebuffered saline (BBS) was used to coat 96-well microtiter plates overnight at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Activated Th2 CD4 ϩ T cells might also be functioning to maintain low levels of the inhibitory receptor Fc␥RIIB on effector cells, as shown by one investigation (29), resulting in the increased activities of Fc␥RI/III-expressing immunologic cell populations. Though CD8 ϩ T-cell function cannot be ruled out altogether in providing some level of tumor immunity, particularly when employing other active immunization modalities, such as plasmid DNA expressing SV40 Tag (2,19,25,26), our previous studies indicated that depletion of CD8 ϩ T cells during the course of rSV40 Tag immunization had no observable effect on the resultant tumor immunity (15). Therefore, we surmise that with regard to tumor immunity from mKSA challenge resulting from rSV40 Tag immunization, SV40 Tag specific antibody opsonizes the function of mKSA tumor cells and effector cells, such as macrophages and NK cells, via ADCC to mediate tumor lysis through expression of Fc␥RI/III.…”
Section: Discussionmentioning
confidence: 99%
“…Studies performed with recombinant Tag (rTag) vaccination revealed a number of critical immune components that function within this system, including Tag-specific antibodies (25,29), natural killer (NK) cells (24,26), and CD8 ϩ T lymphocytes (26). Additionally, targeted depletion of CD4 ϩ T lymphocytes has demonstrated the importance of this cell population in the immune induction phase (22), presumably illustrating the helper function that these cells exert in the activation of other antitumor immune effectors.…”
mentioning
confidence: 99%